Adolescent‐onset heavy cannabis use associated with significantly reduced glial but not neuronal markers and glutamate levels in the hippocampus. (2nd September 2019) - Blest‐Hopley, Grace; O'Neill, Aisling; Wilson, Robin; Giampietro, Vincent; Lythgoe, David; Egerton, Alice; Bhattacharyya, Sagnik
Abstract: Cannabis use has been associated with adverse mental health outcomes, the neurochemical underpinnings of which are poorly understood. Although preclinical evidence suggests glutamatergic dysfunction following cannabis exposure in several brain regions including the hippocampus, evidence from human studies have been inconsistent. We investigated the effect of persistent cannabis use on the brain levels of N ‐acetyl aspartate (NAA) and myoinositol, the metabolite markers of neurons and glia, the site of the main central cannabinoid CB1 receptor, and the levels of glutamate, the neurotransmitter directly affected by CB1 modulation. We investigated cannabis users (CUs) who started using during adolescence, the period of greatest vulnerability to cannabis effects and focused on the hippocampus, where type 1 cannabinoid receptors (CBR1) are expressed in high density and have been linked to altered glutamatergic neurotransmission. Twenty‐two adolescent‐onset CUs and 21 nonusing controls (NU), completed proton magnetic resonance spectroscopy, to measure hippocampal metabolite concentrations. Glutamate, NAA, and myoinositol levels were compared between CU and NU using separate analyses of covariance. CU had significantly lower myoinositol but not glutamate or NAA levels in the hippocampus compared with NU. Myoinositol levels in CU positively correlated with glutamate levels, whereas this association was absent in NU. Altered myoinositol levels may be a marker of glia dysfunction and is consistent with experimental preclinical evidence that cannabinoid‐induced glial dysfunction may underlie cannabinoid‐induced memory impairments. Future studies using appropriate imaging techniques such as positron emission tomography should investigate whether glial dysfunction associated with cannabis use underlies hippocampal dysfunction and memory impairment in CUs. Abstract : Decreased glial marker myoinositol found in the hippocampus of adolescent‐onset adult cannabis users compared to non‐using controls using magnetic resonance spectroscopy.